2017
DOI: 10.26803/ijlter.16.10.10
|View full text |Cite
|
Sign up to set email alerts
|

The use of Social Networks by the Students of a Mexican Public University

Abstract: Abstract. The purpose of this study was to determine the relation between the students' use of digital social networks and the variables of age, time, gender, reasons and their Bachelor's Degree program, in the context of the Faculty of Accounting and Administration (FAA) at a Mexican public university (MPU).The specific objectives were: determine the places and devices used to access their preferred digital social networks; their use and motivations to use these tools. The design of the research was non-exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…displayed the potential of SNSs by incorporating them into the teaching and learning process. This is consistent with a study by Villarruel et al (2017) that found that using digital social networks as a technical tool is regarded as useful and beneficial for teaching and learning in higher education institutions. These results are significant enough to guide future attempts to raise the standard and efficiency of undergraduate students' English language instruction.…”
Section: Discussionsupporting
confidence: 92%
“…displayed the potential of SNSs by incorporating them into the teaching and learning process. This is consistent with a study by Villarruel et al (2017) that found that using digital social networks as a technical tool is regarded as useful and beneficial for teaching and learning in higher education institutions. These results are significant enough to guide future attempts to raise the standard and efficiency of undergraduate students' English language instruction.…”
Section: Discussionsupporting
confidence: 92%
“…It also displayed the potential of SNSs in incorporating in teaching and learning process. (Villarruel, Lima, Rivera, & Morán, 2017) mentioned that from the positive attitude of students towards technological tools are the aspects that will promote Social Networks in the educational development. Table 4.6 shows the frequency of SNS use for the perception of functionality.…”
Section: Resultsmentioning
confidence: 99%
“…It is imperative to consider the students' perspective in the inculcation of SNSs in improving English writing skills. Moreover, (Villarruel et al, 2017) stated that the usage of digital social networks as a technical instrument that is regarded as useful and beneficial for teaching and learning in higher education institutions needs to be reconsidered.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth to state here that students showed a positive attitude towards the use of digital technologies as a solution that can increase the student-supervisor relationship. But, the introducing ICT is one of the main challenges since it modifies the forms of interaction (Villarruel, Lima, Rivera, & Morán, 2017). Also, students' workload prevents students and supervisors from regular meeting.…”
Section: Student-supervisor Relationshipsmentioning
confidence: 99%